PENGARUH RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), DAN DEBT EQUITY RATIO (DER) TERHADAP HARGA SAHAM Studi Pada Perusahaan Makanan dan Minuman yang Go Public di Bursa Efek Indonesia (BEI) - Yeyen Novenia; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
One source of funds obtained by the company is derived from the sale of shares. Stock price changes up or down time by time, and it is influenced by many factors. This research was conducted to examine the effect of Return On Equity (ROE), Earning Per Share (EPS), Debt To Equity Ratio (DER) on Stock Price Study on Food and Beverage Companies Go Public in Indonesia Stock Exchange (IDX) Year 2011-2015. The data used in this research is a secondary data obtained from Indonesia Stock Exchange. Analysis of data using multiple linear regression analysis with SPSS 16. while hypothesis testing using t-test and test-F at a significance level of 5%. The classical assumptions test used in this reasearch include normality, multicolinearity, heteroscedasticity and autocorrelation test. Based on the research result that the of Return on Equity (ROE) a significant positive effect on Stock Price. Meanwhile, Earning Per Share (EPS) and Debt To Equity Ratio (DER) has negative affect on the stock price. Simoultaneously there is a significant effect between Return On Equity (ROE), Earning Per Share (EPS), Debt To Equity Ratio (DER) on Stock Price. For investors who want to invest stocks, should pay attention to the level of Return On Equity (ROE) too, as in this research say that Earning Per Share provides the most powerful influence on Stock Price.Keywords : Return On Equity (ROE), Earning Per Share (EPS), Debt Equity Ratio (DER), Stock Price.